2014
DOI: 10.1371/journal.pone.0108659
|View full text |Cite
|
Sign up to set email alerts
|

Both Central and Peripheral Auditory Systems Are Involved in Salicylate-Induced Tinnitus in Rats: A Behavioral Study

Abstract: ObjectiveThis study was designed to establish a low dose salicylate-induced tinnitus rat model and to investigate whether central or peripheral auditory system is involved in tinnitus.MethodsLick suppression ratio (R), lick count and lick latency of conditioned rats in salicylate group (120 mg/kg, intraperitoneally) and saline group were first compared. Bilateral auditory nerves were ablated in unconditioned rats and lick count and lick latency were compared before and after ablation. The ablation was then per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In particular, the authors found that in rats with evidence of tinnitus, activity was generally elevated in the auditory brainstem, with significant elevation in the cerebellar paraflocculus, the posterior ventral cochlear nucleus, and the inferior colliculus (Brozoski et al, 2007). Chen et al reported changes in the cerebellum of rats shortly after tinnitus was induced with a high dose of salicylate (Chen et al, 2014). This evidence could limit the use of the cerebellum for normalization, resulting in a sub-optimal structure for data normalization in certain circumstances and in particular when variations in brain activity in this structure are detectable during tasks or pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the authors found that in rats with evidence of tinnitus, activity was generally elevated in the auditory brainstem, with significant elevation in the cerebellar paraflocculus, the posterior ventral cochlear nucleus, and the inferior colliculus (Brozoski et al, 2007). Chen et al reported changes in the cerebellum of rats shortly after tinnitus was induced with a high dose of salicylate (Chen et al, 2014). This evidence could limit the use of the cerebellum for normalization, resulting in a sub-optimal structure for data normalization in certain circumstances and in particular when variations in brain activity in this structure are detectable during tasks or pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that the central auditory system largely contributes to the salicylate-induced effects on neuronal activity and auditory phantom perceptions like tinnitus, even after disconnection of the auditory periphery [ 54 , 75 , 76 ]. In the present data, the calcium-related neuronal activity was increased after systemic application of a sodium salicylate solution in several investigated brain structures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that different dosages of SS exposure can trigger tinnitus [17,36]. SS-induced hearing threshold shifts are largely dose-dependent.…”
Section: Neural Plasticitymentioning
confidence: 99%
“…SS, an active component of the nonsteroidal anti-inflammatory drug aspirin, has been commonly used to generate tinnitus in animals [ 17 ]. SS is an anti-inflammation drug used to manage rheumatoid arthritis at therapeutic dose; SS inhibits cyclooxygenase activity and prostaglandin synthesis.…”
Section: Introductionmentioning
confidence: 99%